Telecommuting and Normative Commitment of Employees in a Technology Firm: After Effects of Covid-19 Pandemic - Sholesi, Olayinka Yusuf; Matthew, Awotunde Olusegun; Olorunisola, Kolawole Ibukun (Journal of Economics and Behavioral Studies, 2023)
The recent trend in the world of work has made it expedient for organizations to adopt various flexible work practices such as telecommuting and this is affecting the normative commitment of employees. The study examined telecommuting and the normative commitment of employees in a technology firm. The study adopted the descriptive survey research design. The population of the study is (160) one hundred and sixty and using the Krecjie and Morgan sample size determination formula the sample size of (113) one hundred and thirteen was arrived at. One hundred and thirteen copies of the questionnaire were distributed, purposive sampling techniques were used and three hypotheses were tested using person-product moment correlation and multiple regression using S.P.S.S 27.0 version. The findings revealed that there is a 39.1% weak relationship between remote work and normative commitment and a 97.8% strong relationship between telework and normative commitment. The study further revealed that remote work and telework account for 95.6% of normative commitment. The study concluded that telework is the most significant variable driving normative commitment. However the study recommended among others that management should make it expedient for their telecommuter employees to report to their agency worksite frequently to prevent physical and psychological isolation and there should be constant engagement between the telecommuter employees by putting in place effective online tracking mechanisms to monitor them, also management should give them a sense of belonging, this will help discourage moonlighting.